Perancangan Proses Bisnis Pemesanan Pada Kedai Kopi Menggunakan Simulasi BPMN - Widhyaestoeti, Dahlia; Reza Zainul Ichwan; Fitria Rachmawati; Zulkarnaen Noor Syarif; Jejen Jaenudin (LPPM STIKOM Dinamika Bangsa, 2025)
The increasing number of coffee lovers is evident from the growing number of coffee shops in Bogor City. To maintain competitiveness in today's digital era, innovative business process ideas are needed. Coffee shops currently lack an application that is able to make customers feel served quickly. Business process simulation of the selection of QR Code technology for the problem of selecting a menu in the ordering process to be effective, using the BIZAGI Modeler application. The results of the BPMN simulation using BIZAGI Modeler, which begins with the identification of ordering process activities in the form of BPMN diagrams, time analysis and resource analysis. Assuming 50 customers per day, an average of 14 minutes is required to complete the ordering process for each customer, and it takes around Rp. 156,800 per day to pay 5 employees.